1997
DOI: 10.1007/s002619900176
|View full text |Cite
|
Sign up to set email alerts
|

Anastomoses between the spermatic and visceral veins:a retrospective study of 500 consecutive patients

Abstract: Visceral-spermatic vein communications are classified by number, morphology, and site. Percutaneous sclerotherapy could be optimized when performed caudally to these communications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The scarcity of such references contrasts with the published epidemiological data, which reveal abnormal communications between the left colic and left testicular veins in 7.8% (Salerno et al, ) to 9.2% (Bigot et al, ) of cases, described as a venous trunk with competent valves (5.1%), or communicating venules (3.1%), or single/double anastomoses (1%), with only an outline estimate (77%) reported by Wishahi (). However, despite the hypothetical prevalence of this anatomical variation, some urologists and interventional radiologists report that they cannot correctly visualize it by intraoperative phlebography, although they are aware of its possible presence and check carefully (Fulcoli et al, ; Vicini et al, ).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The scarcity of such references contrasts with the published epidemiological data, which reveal abnormal communications between the left colic and left testicular veins in 7.8% (Salerno et al, ) to 9.2% (Bigot et al, ) of cases, described as a venous trunk with competent valves (5.1%), or communicating venules (3.1%), or single/double anastomoses (1%), with only an outline estimate (77%) reported by Wishahi (). However, despite the hypothetical prevalence of this anatomical variation, some urologists and interventional radiologists report that they cannot correctly visualize it by intraoperative phlebography, although they are aware of its possible presence and check carefully (Fulcoli et al, ; Vicini et al, ).…”
Section: Discussionmentioning
confidence: 90%
“…As previously stated (Lechter et al, ), modern anatomy textbooks often mention anatomical variations and atypical communications of the above‐mentioned portal‐systemic anastomoses only summarily, rarely stressing the anastomotic communication between the left colic vein (portal system) and left testicular vein (systemic). Nevertheless, this anastomosis is clinically relevant in daily practice for clinicians and surgeons (Bigot et al, ). (a) Anastomoses between the gonadal and portal venous systems are commonly recognized by surgeons as small collateral veins that bleed readily during dissection of the colonic fascia (Donovan and Winfield, ), (b) Whenever there is thrombosis in the mesenteric venous system it causes necrosis of the small bowel more frequently than necrosis of the colon, possibly because of a number of anastomoses between the gonadal and colonic veins (Cokkinis, ), (c) Likewise, mesenteric infarction causes proximal rather than distal necrosis, and ligature of the superior mesenteric vein can be uneventful when performed on patients with a preexisting occlusion of the portal vessels (Linton, ), (d) Moreover, asymptomatic portal thrombosis extending to the distal part of the gonadal veins has been reported in patients with acute colonic inflammatory disease, diverticulitis, Crohn's disease, ulcerative colitis, pseudomembranous colitis, and appendicular abscess (Jain and Jeffrey, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies based on venography and with large number of patients report a bilateral varicocele in 25% [8][9][10]. In studies using different diagnostic tools, bilateral varicocele was reported in a range between 40% and 60% [11][12].…”
Section: Presentation Incidence and Epidemiology Of Varicocelesmentioning
confidence: 99%